CINESIOTERAPIA PERINEAL EM MULHERES COM DÉFICIT MUSCULAR NO ASSOALHO PÉLVICO E COM UMA ÚNICA VIA DE PARTO: ensaio clínico - Duarte, Thaiana Bezerra (2012)
BACKGROUND: Pregnancy and delivery route influence the strength of pelvic floor muscles, which are considered risk factors for the onset of urinary incontinence and genital dystopias. OBJECTIVES: To evaluate the effects of kinesiotherapy in the pelvic floor muscles in women with a single delivery. METHODS: Participants were 503 women who responded to the protocol record, 297 (59.0%) aged between 35 and 45 years underwent functional evaluation of the pelvic floor by bidigital touch and perineometer. There were 165 (32.8%) women with deficiency on muscles strength participating in the trial, which were allocated into two groups according to the delivery route (A - vaginal delivery and B - abdominal delivery). They were randomized into groups A1 (n = 44) and B1 (n = 42), and were submitted to kinesiotherapy and groups A2 (n = 39) and B2 (n = 40) without kinesiotherapy. The protocol had perineal contraction exercises in the supine, sitting and standing posture and was performed twice a week for a total of 15 sessions. Statistical analysis used the chi-square test, Mann-Whitney test, Z test, Kruskall Wallis test, and ANOVA one criterion, the Spearman Correlation Coefficient, the Pearson Correlation Coefficient and PHI, with significance level 0.05. RESULTS: As the result of the kinesiotherapeutic protocol by comparing the force of contraction of the pelvic floor before and after application of kinesiotherapy compared to those without kinesiotherapy, there was significant increase in strength on women with both routes of delivery, by the both methods of evaluation (p < 0.0001). Among the variables possibly associated with the DFMAP, only parity was statistically significant (p ˂ 0.0001). CONCLUSIONS: The protocol proposed proved to be effective in the increase of pelvic floor muscle s strength at the assessment by both methods of evaluation. The delivery route was not responsible for weakening perineal but parity, demonstrating that the perineal muscles strength is inversely proportional to the number of births, suggesting that kinesiotherapy during pregnancy may be an alternative to prevent the weakening of pelvic floor.